Clinical Implication of Individually Tailored Segmentation Method for Distorted Hypothalamus in Craniopharyngioma - Hong, A Ram; Lee, Miwoo; Lee, Jung Hyun; Kim, Jung Hee; Kim, Yong Hwy; Choi, Hyung Jin (Frontiers in Endocrinology, 2021)
Objective: Several attempts have been done to capture damaged hypothalamus (HT) using volumetric measurements to predict the development of hypothalamic obesity in patients with craniopharyngioma (CP). This study was to develop a novel method of HT volume measurement and examine the associations between postoperative HT volume and clinical parameters in patients with CP. Methods: We included 78 patients with adult-onset CP who underwent surgical resection. Postoperative HT volume was measured using T1- and T2-weighted magnetic resonance imaging (MRI) with a slice thickness of 3 mm, and corrected for temporal lobe volume. We collected data on pre- and postoperative body weights, which were measured at the time of HT volume measurements. Results: The corrected postoperative HT volume measured using T1- and T2-weighted images was significantly correlated (r=0.51 [95% confidence interval (CI) 0.32 to 0.67], P<0.01). However, HT volume was overestimated using T1-weighted images owing to obscured MR signal of the thalamus in patients with severe HT damage. Therefore, we used T2-weighted images to evaluate its clinical implications in 72 patients with available medical data. Postoperative HT volume was negatively associated with preoperative body weight and preoperative tumor volume (r=–0.25 [95% CI -0.45 to -0.04], P=0.04 and r=–0.26 [95% CI -0.40 to -0.15], P=0.03, respectively). In the subgroup analysis of CP patients who underwent primary surgery (n=56), pre- and postoperative body weights were negatively associated with HT volume (r=–0.30 [95% CI -0.53 to -0.03], P=0.03 and r=–0.29 [95% CI -0.53 to -0.02], P=0.03, respectively). Conclusions: Adult-onset CP patients showed negative associations between postoperative HT volume and preoperative/postoperative body weight using a new method of HT volume measurement based on T2-weighted images.